From student to global citizen - Zakka, Janine Saba (2010)
The 21st century witnessed the development of the knowledge-based-economy due to globalization and the advancement of technology. Creation of wealth in this type of economy is through knowledge that equips the future graduate with the necessary skills to compete globally. The increasing importance of knowledge emphasized the role of the education programs applied by universities in educating the future graduates to become global citizens. Previous research described the merits of liberal education in forming the global citizen. This study investigates the role of the existing liberal education curriculum and its content in developing the global citizen from the point of view of the students and graduates of the Lebanese American University (LAU). A survey and interviews with students and graduates of LAU were used to gather the data needed. While the majority of the responses approved that LAU’s liberal education program provides the characteristics and skills needed to form a global citizen, the researchers suggest that for a liberal education program to be applied and accepted in a developing country, it has to be adapted to the cultural, financial, and economical needs of that country